The impact of growth indicators on value creation A study of a sample of listed firms on Casablanca Stock Exchange for the period 2009-2019 - ameni, lamia; haguiga, mohamed (Journal of Research in Finance and Accounting, 2022)
This study aims to examine the effect of growth indicators on shareholder value creation by study case of listed firms on the Casablanca Stock Exchange for the period 2009-2019, using one of the dynamic models which is the Self-Regression of Errors (VAR). The results of this study indicate that the growth indicators effect shareholder value creation of the studied firms.